PENGARUH SURPLUS ARUS KAS BEBAS DAN KUALITAS AUDIT TERHADAP MANAJEMEN LABA - Tsania Rahmawati (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2020)
The purpose of this research is to examine the effect of surplus free cash flow, audit quality, and the interaction between surplus free cash flow and audit on earnings management. This study uses secondary data in the form of annual reports and financial statements of manufacturing companies listed on the Indonesia Stock Exchange in 2015 and 2016. The sampling method used in this study was purposive sampling. The total research sample is 48 samples. The results showed that surplus free cash flow has a positive effect on earnings management, audit quality significantly influences earnings management, but the interaction between surplus free cash flow and audit quality has no impact on earnings management.